The Effect of Training and Individual Characteristics on Employee Performance Mediated By Employee Competence at the Office of the Class I Airport Organizing Unit in Papua - Agus Kurniawan; Meinarni Asnaw; Ernik Yulianna (Cakrawala Repositori IMWI, 2023)
Due to the vital role of airports in regional development and progress, this study examines the effect of training, individual characteristics, and competencies on employee performance at the Papua Class I Airport Organizing Unit (UPBU) Office. In addition, this study also tested competency variables as mediators. This research is a quantitative study. The research data was obtained by distributing questionnaires to 220 employees at the UPBU Class I Offices in Merauke, Wamena, and Sorong. Only 129 questionnaires can be used as research data. The data analysis method used is path analysis with the help of SPSS software version 25. The results of this study show that training and individual characteristics have a positive and significant effect on employee performance and competence. Competence affects employee performance and can mediate the relationship between training and individual characteristics to employee performance.